Impact of Seed Exudates on Growth and Biofilm Formation of Bacillus amyloliquefaciens ALB629 in Common Bean - Martins, Samuel J.; Medeiros, Flávio H. V.; Lakshmanan, Venkatachalam; Bais, Harsh P. (Frontiers in Microbiology, 2018)
We aimed to unravel the events which favor the seed-rhizobacterium Bacillus amyloliquefaciens strain ALB629 (hereafter ALB629) interaction and which may interfere with the rhizobacterium colonization and growth on the spermosphere of common bean. Seed exudates from common bean were tested in vitro for ALB629 biofilm formation and bacterial growth. Furthermore, the performance of ALB629 on plant-related variables under drought stress were checked. Seed exudates (1 and 5% v/v) increased ALB629 biofilm formation. Additionally, the colony forming units for ALB629 increased both in culture and on the bean seed surface. The bean seed exudates up-regulated biofilm operons in ALB629 TasA and EpsD by ca. 2- and 6-fold, respectively. The high-performance liquid chromatography (HPLC)-coupled with MS showed that malic acid is present as a major organic acid component in the seed exudates. Seeds treated with ALB629 and amended with malic acid resulted in seedlings with a higher bacterial concentration, induced plant drought tolerance, and promoted plant growth. We showed that seed exudates promote growth of ALB629 and malic acid was identified as a major organic acid component in the bean seed exudates. Our results also show that supplementation of ALB629 induced drought tolerance and growth in plants. The research pertaining to the biological significance of seed exudates in plant-microbe interaction is unexplored field and our work shows the importance of seed exudates in priming both growth and tolerance against abiotic stress.